Autophagy activation by novel inducers prevents BECN2-mediated drug tolerance to cannabinoids. Issue 9 (1st September 2016) - Kuramoto, Kenta; Wang, Nan; Fan, Yuying; Zhang, Weiran; Schoenen, Frank J.; Frankowski, Kevin J.; Marugan, Juan; Zhou, Yifa; Huang, Sui; He, Congcong
ABSTRACT: Cannabinoids and related drugs generate profound behavioral effects (such as analgesic effects) through activating CNR1 (cannabinoid receptor 1 [brain]). However, repeated cannabinoid administration triggers lysosomal degradation of the receptor and rapid development of drug tolerance, limiting the medical use of marijuana in chronic diseases. The pathogenic mechanisms of cannabinoid tolerance are not fully understood, and little is known about its prevention. Here we show that a protein involved in macroautophagy/autophagy (a conserved lysosomal degradation pathway), BECN2 (beclin 2), mediates cannabinoid tolerance by preventing CNR1 recycling and resensitization after prolonged agonist exposure, and deletion of Becn2 rescues CNR1 activity in mouse brain and conveys resistance to analgesic tolerance to chronic cannabinoids. To target BECN2 therapeutically, we established a competitive recruitment model of BECN2 and identified novel synthetic, natural or physiological stimuli of autophagy that sequester BECN2 from its binding with GPRASP1, a receptor protein for CNR1 degradation. Co-administration of these autophagy inducers effectively restores the level and signaling of brain CNR1 and protects mice from developing tolerance to repeated cannabinoid usage. Overall, our findings demonstrate the functional link among autophagy, receptor signaling and animal behavior regulated by psychoactive drugs, and develop a new strategy to prevent tolerance and improve medical efficacy of cannabinoids by modulating the BECN2 interactome and autophagy activity.